Review of interruptions in a pediatric subspecialty outpatient clinic. - Tyler Lee; Hinette Rosario; Elizabeth Cifuentes; Jiawei Cui; Emery C Lin; Victoria A Miller; Henry C Lin (PLoS ONE)
Introduction The objective of this study was to describe interruptions in the pediatric ambulatory setting and to assess their impact on perceived physician communication, patient satisfaction and recall of provided physician instructions. Methods An observational study was performed at the Children's Hospital of Philadelphia, Pediatric Gastroenterology clinic. Participation consisted of video recording the clinic visit and the caregiver completed post-visit surveys on communication and satisfaction. Video recordings were coded for interruptions, which were divided into 3 main categories: Visit Associated, Pediatric Associated, and Unanticipated. An interruption rate was calculated and correlated with the following outcome variables to assess the impact of interruptions: caregiver satisfaction, caregiver perception on the quality of physician communication, and caregiver instruction recall. Results There were 675 interruptions noted in the 81 clinic visits, with an average of 7.96 (σ = 7.68) interruptions per visit. Six visits had no interruptions. The Patient was the most frequent interrupter. Significantly higher interruption rates occurred in clinic visits with younger patients (<7 years old) with most of the interruptions being Pediatric Associated interruptions. There was minimal correlation between the clinic visit interruption rate and caregiver satisfaction with the communication, caregiver perception of quality of communication, or caregiver instruction recall rate. Conclusion The effect of interruptions on the pediatric visit remains unclear. Interruptions may be part of the communication process to ensure alignment of the patient's agenda. Additional studies are needed to help determine the impact of interruptions and guide medical education on patient communication.